Exploration of the Potential of Gambir Leaf Extract (Uncaria gambir Roxb.) from Sutera, Pesisir Selatan as a Feed Additive to Improve Fiber Digestibility and Suppress Methane Emissions of Ruminants - Roni Pazla; Asmuddin Natsir; Rahmat Hidayat; Urip Rosani; Nurzainah Ginting; Antonius; Zaitul Ikhlas; Aslizah Mohd. Haris; Yelly Fitri (Andalasian Livestock, 2025)
This study explored the potential of gambir leaf extract (Uncaria gambir Roxb.) from Sutera, South Pesisir Regency, West Sumatra, as a natural feed additive to improve fiber digestibility and suppress methane emissions in rumen fermentation. The study was conducted in vitro using fiber-based rations added with gambir extract at 0%, 0.5%, 1%, and 2%. Parameters observed included digestibility of NDF, ADF, cellulose, hemicellulose, and methane gas production. Results showed that adding gambir extract up to 2% significantly increased fiber digestibility and decreased methane production compared to the control. This study proves that local gambir extract has the potential as an environmentally friendly feed additive to support the efficiency and sustainability of ruminant farming.